The German Version of the Strengths Use Scale: The Relation of Using Individual Strengths and Well-being - Huber, Alexandra; Webb, Dave; Höfer, Stefan (Frontiers in Psychology, 2017)
Theoretical perspectives in positive psychology have considered the possession and use of strengths equally but in applied research more studies focused on having them, probably due to the absence of psychometrically adequate scales. Therefore, the aim of this study was to assess the psychometric characteristics of the German language version of the Strengths Use Scale (SUS) and to explore relationships between strengths use and several indicator measures of well-being: the presence of positive and the absence of negative affect, self-esteem as identity aspect, vitality as self-regulatory resource, and stress for capturing the evaluation of difficulties and obstacles impinging on well-being. The original English version of the SUS was translated following recommended independent forward-backward translation techniques. Exploratory and confirmatory factor analyses were conducted, including a German-speaking convenience sample of university students (N=374). Additionally, the relations of strengths use and well-being indicators were analyzed. Factorial validity revealed a single-factor structure of the German version of the SUS, explaining 58.4% variance (factor loadings: .58 to .86), approving the scale’s design and showing high internal consistency (Cronbach’s α .95). The hypothesized positive relationships of strengths use with positive affect, self-esteem and vitality were confirmed as well as the negative relationships with negative affect and stress. The German version of the SUS is psychometrically sound and data indicate that individual strengths use and well-being related measures interact. The instrument can be recommended for future research questions such as if and how the promotion of applying individual strengths during education enhances levels of well-being, or how the implementation of strengths use in job-design guidelines or working conditions can result in higher levels of well-being or healthiness.